Impact of pandemic on ocular trauma trends among infants and toddlers, 2017-2021 - Chauhan, Muhammad Z.; Tetelbom, Pedro; Elhusseiny, Abdelrahman M.; Phillips, Paul H.; Sallam, Ahmed B.; Uwaydat, Sami H. (Digital Journal of Ophthalmology, 2023)
Introduction To investigate the epidemiologic trends in pediatric ocular injuries caused by consumer products (CP) in children 3 years of age and under from 2017 to 2021 in the United States. Methods We analyzed data from the US Consumer Product Safety Commission (USCPSC) National Electronic Injury Surveillance System (NEISS) for the years 2017-2021. We used Pearson χ2 tests to determine differences in demographic characteristics, diagnoses, location of the injury, product category, and final disposition between 2017 and 2019 and 2020 and 2021. A logistic regression model was run with chemical-burn-related injuries as the dependent variable and the time periods (pre-pandemic vs post-pandemic) as the primary independent variable adjusting for age, sex, race, and injury location. Results The national-level estimate of ocular injuries in infants and toddlers was 51,250 (95% CI, 30,471-72,030). Most injuries occurred at home. The proportion of cases caused by cleaning products increased from 35.48% (95% CI, 31.39-39.79) in 2017-2019 to 41.54% (95% CI, 36.61-46.64) in 2020-2021, with a significant decline in projectile ocular injuries from 0.89% (95% CI, 0.35-2.25) to 0.12% (95% CI, 0.03-0.45) (P = 0.037). The proportion of patients diagnosed with chemical-burn-related injuries increased significantly from 23.34% (95% CI, 19.73-27.38) in the pre-pandemic period to 31.63% (95% CI, 26.98-36.69) in the post-pandemic period (P = 0.048). After adjusting for confounding variables, the odds of sustaining a chemical-burn-related injury in the post-pandemic period were 1.51 times higher than in the pre-pandemic period (95% CI, 1.10-2.08). Conclusions We found that the percentage of patients diagnosed with chemical-burn-related injuries increased significantly in the post-pandemic period with a decline in injuries caused by projectiles. The observed differences in ocular trauma presentations in our study may be due to changes in the home environment caused by the COVID-19 pandemic.